Robotic arm-assisted versus manual total hip arthroplasty: a propensity score matched cohort study. Issue 1 (1st January 2021) - Clement, Nicholas D.; Gaston, Paul; Bell, Allison; Simpson, Philip; Macpherson, Gavin; Hamilton, David F.; Patton, James T.
Abstract : Aims: The primary aim of this study was to compare the hip-specific functional outcome of robotic assisted total hip arthroplasty (rTHA) with manual total hip arthroplasty (mTHA) in patients with osteoarthritis (OA). Secondary aims were to compare general health improvement, patient satisfaction, and radiological component position and restoration of leg length between rTHA and mTHA. Methods: A total of 40 patients undergoing rTHA were propensity score matched to 80 patients undergoing mTHA for OA. Patients were matched for age, sex, and preoperative function. The Oxford Hip Score (OHS), Forgotten Joint Score (FJS), and EuroQol five-dimension questionnaire (EQ-5D) were collected pre- and postoperatively (mean 10 months (SD 2.2) in rTHA group and 12 months (SD 0.3) in mTHA group). In addition, patient satisfaction was collected postoperatively. Component accuracy was assessed using Lewinnek and Callanan safe zones, and restoration of leg length were assessed radiologically. Results: There were no significant differences in the preoperative demographics (p ≥ 0.781) or function (p ≥ 0.383) between the groups. The postoperative OHS (difference 2.5, 95% confidence interval (CI) 0.1 to 4.8; p = 0.038) and FJS (difference 21.1, 95% CI 10.7 to 31.5; p < 0.001) were significantly greater in the rTHA group when compared with the mTHA group. However, only the FJS was clinically significantly greater. There was no difference in the postoperative EQ-5D (difference 0.017, 95% CI -0.042 to 0.077; p = 0.562) between the two groups. No patients were dissatisfied in the rTHA group whereas six were dissatisfied in the mTHA group, but this was not significant (p = 0.176). rTHA was associated with an overall greater rate of component positioning in a safe zone (p ≤ 0.003) and restoration of leg length (p < 0.001). Conclusion: Patients undergoing rTHA had a greater hip-specific functional outcome when compared to mTHA, which may be related to improved component positioning and restoration of leg length. However, there was no difference in their postoperative generic health or rate of satisfaction. Cite this article: Bone Joint Res 2021;10(1):22–30.